Uganda : Technical Assistance Report-Report on the Monetary and Financial Statistics Mission. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2017)
This Technical Assistance Report discusses technical advice and recommendations given by the IMF mission to the authorities of Uganda regarding compilation of the sectoral balance sheet of other financial corporations using the IMF's Standardized Report Form (SRF-4SR). The mission's recommendations are aimed at improving (1) the collection and compilation of monetary and financial statistics based on the IMF's Monetary and Financial Statistics Manual (MFSM) and (2) the collection of data on intra-East African Community positions with the objective of compiling consolidated regional monetary aggregates. The compilation of monetary statistics and the expansion of its institutional coverage based on the MFSM will improve data quality and usefulness for policy analysis.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet